TOURIST TRANSPORTATION PREFERENCE IN BROMO MOUNTAIN ( A Case Study in Taman Nasional Bromo Tengger Semeru (TNBTS) ) - Bramantyo, Dio Bagus; Syafitri, Wildan (Jurnal Ilmiah Mahasiswa FEB, 2016)
This study is aimed to analyze the factors affecting tourist transportation preference in Bromo Mountain. Using linear logistic model on 100 respondents including domestic and international tourist, this study divided into three kind of transportation that is used in Bromo, including on foot, horse and car/jeep. Gender, type of tourist, and occupation are significant to choose on foot as the transportation. Besides, ages, type of tourist, occupation, and purposes is significant to choose horse as the transportation. On the other hand, gender, ages, occupation and purposes are significant to choose car as the transportation. Keywords: Tourist transportation preference, bromo